International business. - Woods, Margaret, 1954- (International Thomson Business, 1996)
This book is designed for a first course in international business, either aspart of a general business and management degree, or for post-experience courses. Each chapter is self-contained and can be used as class reading in preparation for a lecture. The case studies at the end of each chapter provide tutorial material and are accompanied by discussion questions. It is written in an accessible style which is intended to help students learn by means of practical examples and is an easy-to-use text for self-tuition.